Artful pedagogy: (En)visioning the unfinished whole. Issue 1 (2nd January 2016) - Shields, Sara Scott; Guyotte, Kelly W.; Weedo, Nicole
ABSTRACT: The hum of florescent lights still drone quietly in the background just as they did in the high school art classrooms of the authors, only now they are teaching research methods and educational theory and practice in the academy, not sculpture, ceramics, drawing, or painting 1 . Once high school art educators, drawn to teaching and learning with and through the arts, the vantage points of the authors have now shifted as they find themselves situated at two large research universities. In these higher education spaces the authors are once again finding ways to artfully engage in the reciprocal process of teaching and learning. Although the locations have changed, the authors still feel seduced by the world of art and all the possibilities therein.